PENINGKATAN PERAN ISTRI PETANI KELAPA: ANALISIS TANTANGAN DAN POTENSI MENUJU KEBERLANJUTAN USAHATANI - Winarti, Lili; Permadi, Rokhman (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Empowering women in the context of agricultural sustainability is an important and relevant issue. However, there are challenges and obstacles that need to be addressed in efforts to empower women farmers. Therefore, an in-depth analysis of the roles, challenges, and potentials of coconut farmer's wives in women's empowerment is necessary. The aim of this research is to evaluate the roles of coconut farmer's wives based on their potentials and the challenges they face, with the goal of supporting the sustainability of coconut farming. A Strengths, Weaknesses, Opportunities, and Threats (SWOT) framework combined with an Analytical Hierarchy Process (AHP) framework is used to analyze the perceptions of experts regarding the roles of coconut farmer's wives in the research location. The research findings indicate that the most prominent threat to the role of women farmers is the frequent changes in agricultural policies that can affect prices and the lack of training programs for women coconut farmers. Meanwhile, the prominent weaknesses affecting the role of women coconut farmers in the research location are the frequent limitations in accessing productive resources such as capital, land, technology, and training. The results obtained from this research can provide knowledge and understanding to various stakeholders regarding the most crucial issues to consider in formulating policies to enhance the role of women farmers